Preoperative SGLT2 Inhibitor Use and Outcomes After Major Cardiac Procedures: A Propensity Score-Matched Analysis of the TriNetX Network - Mirza Muhammad Hadeed Khawar; Faizan Ahmed; Mohab Elnashar; Cheryl Vanessa Lewis; Minahil Shahid; Ali Asgher Shuja; Fatima Afzal; Naheed Sajjad; Muhammad Amir Khan; Meeran Atta; Umair Arshad; Muneeb Khawar; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Sodium–glucose cotransporter-2 (SGLT2) inhibitors improve cardiorenal outcomes in patients with diabetes, heart failure, and chronic kidney disease. Their association with perioperative outcomes after major cardiac procedures remains uncertain. Methods: In this retrospective cohort study using the TriNetX U.S. Collaborative Network, adults (≥18 years) undergoing cardiac procedures were identified. Patients with documented SGLT2 inhibitor use within 1 year before the index procedure were compared with non-users. Risk ratios (RR), risk differences, Kaplan–Meier survival curves, and Cox models were used for analysis. Results: Of 150,724 patients identified, 7526 propensity score-matched pairs were analyzed. The matched cohorts had a mean age of 65.8 ± 10.6 years and were predominantly male (70.5% male, 29.5% female). Preoperative SGLT2 inhibitor use was associated with significantly lower all-cause mortality at 30 days (1.3% vs. 2.3%; RR 0.566 [95% CI 0.443–0.722], p < 0.001), 90 days (2.2% vs. 3.4%; RR 0.643, p < 0.001), and 1 year (3.8% vs. 5.8%; RR 0.657, p < 0.001). MACE rates were similar between groups at all time points. Acute kidney injury at 30 days was lower with SGLT2 inhibitors (15.4% vs. 17.7%; RR 0.870, p < 0.001), whereas hospital admission rates were higher (76.4% vs. 68.7%; RR 1.111 [95% CI 1.089–1.133], p < 0.001). These associations were consistent in diabetes-only and obesity-only subgroups and in a 30-day landmark sensitivity analysis. Conclusions: In this large, contemporary, multi-institutional propensity score-matched cohort, preoperative SGLT2 inhibitor use was associated with reduced all-cause mortality and acute kidney injury after major cardiac procedures. These real-world findings support the conduct of dedicated randomized trials evaluating perioperative SGLT2 inhibitor therapy.